Mengukur kinerja keuangan syariah melalui Net Profit Margin: Studi kasus Bank Muamalat Indonesia - Fuad, Muhammad Fajrul; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the extent of profit earned by Bank Muamalat Indonesia through the Net Profit Margin (NPM) ratio between 2020 and 2024. NPM serves as the primary tool for assessing a bank’s ability to generate net profit from its total revenue and assessing the operational efficiency of Islamic banks. Data were obtained from Bank Muamalat’s annual financial reports and analyzed descriptively using a trend approach. The findings of this study indicate that Bank Muamalat’s NPM has undergone significant changes. From 2020 to 2021, the NPM was low but stable at 0.41 and 0.42, respectively, due to the pandemic and high operational costs. 2022 was a significant year, as the NPM increased significantly to 1.51 due to cost savings and improved loan quality. However, the NPM declined again to 0.62 in 2023 due to cost pressures and global economic uncertainty. In 2024, the NPM rose again to 0.86, indicating a recovery in profitability. Overall, this trend reflects Bank Muamalat’s ability to adapt in managing its financial performance amidst economic changes.